Identification of patients at high risk for post-discharge venous thromboembolism after hepato-pancreato-biliary surgery: which patients benefit from extended thromboprophylaxis?. Issue 7 (July 2018) - Beal, Eliza W.; Tumin, Dmitry; Chakedis, Jeffery; Porter, Erica; Moris, Dimitrios; Zhang, Xu-feng; Abdel-Misih, Sherif; Dillhoff, Mary; Manilchuk, Andrei; Cloyd, Jordan; Schmidt, Carl R.; Pawlik, Timothy M.
Abstract: Background: The objective of the current study was to define risk factors associated with the 30-day post-operative risk of VTE after HPB surgery and create a model to identify patients at highest risk of post-discharge VTE. Methods: Patients who underwent hepatectomy or pancreatectomy in the ACS-NSQIP Participant Use Files 2011–2015 were identified. Logistic regression modeling was used; a model to predict post-discharge VTE was developed. Model discrimination was tested using area under the curve (AUC). Results: Among 48, 860 patients, the overall 30-day incidence of VTE after hepatectomy and pancreatectomy was 3.2% (n = 1580) with 1.1% (n = 543) of VTE events occurring after discharge. Patients who developed post-discharge VTE were more likely to be white, had a higher median BMI, have undergone pancreatic surgery, had longer median operative times, and to have had a transfusion. A weighted prediction model demonstrated good calibration and fair discrimination (AUC = 0.63). A score of ≥−4.50 had maximum sensitivity and specificity, resulting in 44% of patients being treating with prophylaxis for an overall VTE risk of 1.1%. Conclusions: Utilizing independent factors associated with post-discharge VTE, a prediction model was able to stratify patients according to risk of VTE and may help identify patients who are most likely to benefit from pharmacoprophylaxis.